Understanding Engagement in and Affective Experiences During Physical Activity: The Role of Meditation Interventions. Issue 6 (20th July 2021) - Don, Brian P.; Van Cappellen, Patty; Fredrickson, Barbara L.
Abstract : Supplemental digital content is available in the text. ABSTRACT: Objective: Meditation interventions promote an array of well-being outcomes. However, the way in which these interventions promote beneficial outcomes is less clear. Here, we expanded on prior work by examining the influence of mindfulness and loving-kindness meditation on a key health behavior: physical activity. Methods: To test our hypotheses, we drew upon two randomized intervention studies. In the first study, 171 adults (73.0% female) received 6 weeks of training in either mindfulness meditation or loving-kindness meditation, or were assigned to a control condition. In the second study, 124 adults (60.0% female) were assigned to a 6-week mindfulness or loving-kindness meditation group. Results: Study 1 demonstrated that individuals who received mindfulness training reported sustained levels of physical activity across the intervention period (Pre: mean [standard deviation], or M [SD] = 4.09 [2.07]; Post: M [SD] = 3.68 [2.00]; p = .054), whereas those in the control (Pre: M [SD] = 3.98 [2.25]; Post: M [SD] = 3.01 [2.07]; p < .001) and loving-kindness (Pre: M [SD] = 4.11 [2.26]; Post: M [SD] = 3.45 [1.96]; p < .001) conditions reported lower levels. Study 2 demonstrated those who received mindfulness training experienced increases in positive emotions during physical activity from preintervention to postintervention (Pre: M [SD] = 6.06 [2.51]; Post: M [SD] = 6.54 [2.43]; p = .001), whereas those trained in loving-kindness meditation experienced decreases in positive emotions during physical activity (Pre: M [SD] = 6.45 [2.35]; Post: M [SD] = 6.09 [2.46]; p = .040). Conclusions: These results suggest mindfulness training (but not loving-kindness training) promotes sustained physical activity, and one plausible reason why this occurs is enhanced positive emotion during physical activity.